Health Care Access Brokerage by School Employees for Immigrant Mexican and Indigenous Guatemalan Farmworking Families in a Connecticut Elementary School - Rebecca Campbell-Montalvo; Oxana Sidorova; Miriam Valdovinos; Xiaomei Cong; Ruth Lucas (SAGE Publishing, 2022)
It is known that Florida school employees known as Migrant Advocates facilitate or broker MSF health care access for migrant and seasonal farmworker (MSF) families, but it is not known how states without a Migrant Education Program might also broker MSF health care access. To address this, present study examines the role of school employees in brokering health care access to immigrant Mexican and Indigenous Guatemalan MSF families in Connecticut. Informed by prior work, interviews (n = 12) with parents and elementary school employees showed that (1) a vast array of non-Migrant Advocate school employees, mostly Latinx women, directly brokered physical and psychosocial MSF health care access, often through developing deep social relationships and (2) barriers to brokerage included language inaccessibility, school employee gaps in knowledge of MSF health care needs, and transportation and related structural issues. Importantly, the school's location near MSF homes is an important contributor to the success of the school's brokerage efforts. Findings offer insight into how a school health broker model might be implemented, and advance understandings of MSF health and health care access.